Low Dose Radiotherapy (LDRT) Can Be an Option For Curing COVID-19? - Soma S. Mohammed Amin; Salah Qadir Mahmood; Muhammed Babakir-Mina (Institute of Medico-legal Publications Pvt Ltd, 2021)
In December 2019, the epidemic of Coronavirus Disease 2019 (COVID-19) broke out in Wuhan in China. Symptoms of COVID-19 are non-definite and mild symptoms include: fever, cough. However, elderly and populations with comorbidities such as diabetes, hypertension are more likely to be at risk of severe pulmonary infection and death. Many therapies have been proposed and assed for treating (COVID-19). In April 2020, two papers appeared that suggested clinical trials of low dose radiotherapy (LDRT) for COVID19 pneumonia. Following that, some researchers carried out some studies, and they modify the amount of doses and fractionation. Regarding the aging, some study using a sensitive age that ranged from 18 to 50 years, are more likely to have stochastic effects that cannot analyzed directly as it needs more time to experience these effects. In this review, we analysis the possibility of a low dose radiotherapy that can have in treating COVID-19 pneumonia, by using almost all accessed publications that performed on a low dose radiotherapy (LDRT) for curing bacteria or virus as well as studies that focus on using LDRT for antiinflammatory. We show that LDRT can perform the mitigation and the repair response of the immune system to provide a potential therapy of COVID-19. A single dose of low-dose radiotherapy can be effective in both cost and time and could potentially relieve symptoms of respiratory rapidly. However, such treatment would not be without obstacle and it can be difficult since it is necessary to recognize those few patients who are more benefit from radiation treatment and identifying short and long-term impacts. clinical stage of disease should be known. Additionally, it is not acceptable to report that LDRT would be superior to any type treatment that are currently under taking, until results from clinical trial will be released.